Analysis and measure of novel stereo-garage driven by linear induction motor - Lu Qinfen; Ye Yunyue; Shen Jianxin (Archives of Electrical Engineering, 2015)
The car access time is a key parameter, especially in a huge stereo-garage, where this one should be decreased as much as possible. This paper proposes a novel stereo-garage. Adopting the linear induction motors (LIMs), the system has a simple structure and rapid response capability. In the stereo-garage, several LIMs are installed below the crossbeam on a lifting platform, and several LIMs are fixed on the top of a moving frame. During the operation of LIMs, the moving frame moves forward and backward to reach the required parking place, whereas the crossbeam moves horizontally in order to take or store the vehicle rapidly. All these LIMs are the same and should be designed at a low frequency. The influences of key structure parameters and dynamic performances are investigated, based on FEM. The predicted results are validated by a prototype. Finally, the designed LIMs are successfully applied in two 8-layer stereo-garages.